Islanding detection of distributed generation systems using hybrid technique for multi-machine system - Sindhura S. Sirige; Sallena Choudhury; Jayalakshmi N. S. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Due to depletion of conventional fuels and increase in power demand, many renewable energy sources are being integrated into the electrical grid. One of the major concerns with this integration of these renewable sources with utility grid is unintentional islanding. Many techniques have been proposed to detect unintentional islanding, all of them trying to comply with the IEEE standard 1547. This paper presents an analysis of the hybrid technique to detect the islanding condition of the power system with multi-machine systems. This work aims at analysing the technique against increasing size of the system with increasing number of distributed generators by including practical voltage unbalance formula. The validity of this detection technique is verified using IEEE standard test power systems in MATLAB platform. This method can be used to identify multiple islanding conditions effectively. The simulation results show the effectiveness of the technique to detect islanding condition for multi-machine systems.